The forging of moral leaders in social entrepreneurship: A comparative study from two public welfare organizations in China - Zhang, Shuo; Zhu, Huaixin; Lu, Jihai; Lu, Meili (Frontiers in Environmental Science, 2023)
The youth group with college students as the main body is the main force of public welfare entrepreneurship, and is the effective force of social entrepreneurs in the future. How can college students, who are often self-made and lack entrepreneurial experience, social capital and resources, grow up to be "moral leaders" of social entrepreneurship organizations? And what role does social entrepreneurship education play? No corresponding theoretical explanation has been given in previous studies. In this paper, two public welfare organizations and their founders, namely YinChao Pension Service Center in Yinzhou District, Ningbo City and Ant Public Welfare Service Center in Yuyao City, are taken as examples. The exploratory comparative research method of two cases is adopted, and the perspective is constructed based on personal significance. Through the open decoding analysis, this paper refines the key elements of the individual growth of public entrepreneurs as "moral leaders", including four stages: concept construction stage, moral conflict stage, relationship construction stage and rule construction stage, as well as personal meaning construction strategy and public entrepreneurship education strategy. The research results not only explain how individuals grow up to be "moral leaders" in public welfare organizations through self-meaning construction under the background of public welfare entrepreneurship, and the construction process from individual morality to organization morality system, but also provide a theoretical framework for how to cultivate successful public welfare entrepreneurs, and provide theoretical reference for the sustainable development of public welfare entrepreneurs and public welfare entrepreneurship education in colleges and universities.